Software development hour with Sam Newman : audio collection 2023 (O'Reilly Media, Inc., 2023)
This is the one stop shop for all Software Development Hour interviews of 2023 in their audio format. Keep up-to-date with Sam Newman and his colleagues on their software development journeys.